Comparison of enzyme immunoassays and cell culture for detecting Chlamydia trachomatis. - Mohanty, K C (1986)
Endourethral or endocervical swabs were taken from 403 patients to detect Chlamydia trachomatis by four different methods including standard tissue culture. Two immunoenzyme assays, Chlamydiazyme and IDEIA, were found to be satisfactory and could be valuable for large and busy sexually transmitted disease (STD) clinics.